Identifikasi Parameter Signifikan Dalam Penentuan Prioritas Rencana Pengembangan Daerah Irigasi (DI) Kabupaten Rokan Hulu - Rumeisyah, Rumeisyah; Sandhyavitri, Ari; Fauzi, Manyuk (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Rokan Hulu is one of districts that are members of the Operasi Pangan Riau Mandiri program (OPRM) which is a program implemented by the Riau Province in order to achieve self-sufficiency in rice for the Riau Province in 2013. To support the program, the governments of Rokan Hulu sought to develop rice fields irrigated area. Under budget constraint it is necessary to identify priority in the development plan for the irrigation area.This research discusses prioritization approache in developing of the irrigation areas based from the Analytical Hierarchy Process (AHP) method. Five criteria for development of the irrigation areas are prioritited as follow: technical aspec, economic, environmental, social/cultural and institutional.The results of the AHP analysis obtained the significant parameters as the following order: institutional (45,0%), technical criteria (21,9%), economic criteria (18,6%), Social/Culture criteria (8,6%), and environmental criteria (5,9%). The significant sub-criteria as the following order: the performance of farmer groups P3A, the condition and function of irrigation channel, availability of rehabilitation funds from local government (APBD), the availability of farmers implementing and availability of water resources. The significant irrigation areas are prioritited as follow Kaiti Samo irrigation area (56,9%)I, Menaming irrigation area (19,7%)II, Palis irrigation area (14,2%)III, Perak irrigation area (9,3%)IV.Keywords: analytical hierarchy process, Irrigation areas, Priority, Rokan Hulu